2019
DOI: 10.1007/978-3-030-14850-8_11
|View full text |Cite
|
Sign up to set email alerts
|

Using Kahoot as a Learning Tool

Abstract: O presente trabalho tem como objetivo investigar o uso do "kahoot" como recurso educacional no processo de ensino-aprendizagem para estudantes do ensino médio da área de informática. Para isso, utilizou-se uma abordagem exploratória, descritiva e bibliográfica. A pesquisa foi realizada com 34 alunos do curso técnico em informática para internet do Instituto Federal de Goiás (IFG). Os alunos realizaram as atividades propostas e em seguida responderam a um questionário através de um formulário do GoogleDocs. De … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 6 publications
1
12
0
1
Order By: Relevance
“…This data suggests that Kahoot can create an energetic competitive environment (Baszuk & Heath, 2020) through a game-like learning experience that can considerably affect students' learning. This empirical data confirmed the work of several previous studies (Baszuk & Heath, 2020;Gani et al, 2016;Guardia et al, 2019;Licorish et al, 2018;Martins et al, 2019;Mu & Paparas, 2015;Wang, 2015;Wang & Lieberoth, 2016), which also resulted that the participants enjoyed the competitive elements in Kahoot session. On the contrary, some existing literature reported contradictory findings that the students were not enjoyable with the competitive element in the Kahoot system and the teachers felt anxious that this competitive gaming element made the students experienced anxiety during the Kahoot session (Baydas & Cicek, 2019;Zarzycka-piskorz, 2016).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This data suggests that Kahoot can create an energetic competitive environment (Baszuk & Heath, 2020) through a game-like learning experience that can considerably affect students' learning. This empirical data confirmed the work of several previous studies (Baszuk & Heath, 2020;Gani et al, 2016;Guardia et al, 2019;Licorish et al, 2018;Martins et al, 2019;Mu & Paparas, 2015;Wang, 2015;Wang & Lieberoth, 2016), which also resulted that the participants enjoyed the competitive elements in Kahoot session. On the contrary, some existing literature reported contradictory findings that the students were not enjoyable with the competitive element in the Kahoot system and the teachers felt anxious that this competitive gaming element made the students experienced anxiety during the Kahoot session (Baydas & Cicek, 2019;Zarzycka-piskorz, 2016).…”
Section: Discussionsupporting
confidence: 90%
“…Throughout recent years, many influential academics around the world have been interested in investigating Kahoot incorporated into a broad multidisciplinary context of the study (Esteves et al, 2017;Guardia et al, 2019;Ismail et al, 2019;Kinder & Kurz, 2018;Lee et al, 2019;Martins et al, 2019;Rahman et al, 2018). Those all works of literature agree that Kahoot can potentially facilitate pedagogical practices.…”
mentioning
confidence: 99%
“…A considerable percentage (85.7%) agree that they loved competitive elements provided by Kahoot!. According to Martins et al (2019), the existence of competitive elements in Kahoot! can be a powerful stimulus for the students to actively participate in this game-like quizzes so that it can be highly influential in the development of meaningful learning.…”
Section: Discussionmentioning
confidence: 99%
“…This current study was implemented following the phases suggested by Martins et al (2019). Initially, after following the registration procedure on the site https://kahoot.com/, the researcher prepared an online quiz before the lesson.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation